DNA Modified with Metal Nanoparticles: Preparation and Characterization of Ordered Metal-DNA Nanostructures in a Solution and on a Substrate. (17th February 2016) - Kasyanenko, Nina; Varshavskii, Mikhail; Ikonnikov, Eugenii; Tolstyko, Evgenii; Belykh, Roman; Sokolov, Petr; Bakulev, Vladimir; Rolich, Valery; Lopatko, Konstantin
Abstract : DNA interaction with silver and aluminum nanoparticles in a solution has been investigated with the AFM, SEM, dynamic light scattering, viscometry, and spectral methods. The comparison of DNA interaction with nanoparticles synthesized by the reduction of Ag + ions and with nanoparticles obtained by the electric discharge plasma method was done. DNA metallization in a solution and onn -silicon surface with metal nanoparticles or by the reduction of silver ions after their binding to DNA was executed and studied. It was shown that DNA strands with regular location of silver or aluminum nanoparticles can be prepared. The conditions for the formation of silver nanoparticles and silver nanoclusters on DNA were analyzed.